Cost‐effectiveness of root canal treatment compared with tooth extraction in a Swedish Public Dental Service: A prospective controlled cohort study - Emma Wigsten; Thomas Kvist; Magnus Husberg; EndoReCo; Thomas Davidson (Wiley, 2023)
Abstract Objectives To evaluate the cost‐effectiveness of root canal treatment (RCT) compared with a tooth extraction in a general dental practice setting, with reference to cost per quality‐adjusted life‐year (QALY) gained over 1 year. Material and Methods This is a prospective controlled cohort study based on patients either starting RCT or undergoing extraction at one of six Public Dental Service clinics in the county of Västra Götaland, Sweden. From a total of 65 patients, 2 comparable groups were formed: 37 started RCT and 28 underwent extraction. A societal perspective was used for the cost calculations. QALYs were estimated, based on the EQ‐5D‐5L given to the patients at their first treatment appointment and then after 1, 6, and 12 months. Results The total mean cost of RCT ($689.1) was higher than for extraction ($280.1). For those patients whose extracted tooth was replaced, the costs were even higher ($1245.5). There were no significant intergroup differences in QALYs, but a significant improvement in health state values in the tooth‐preserving group. Conclusions In the short term, extraction was cost‐effective compared with preserving a tooth with RCT. However, the potential need for future replacement of the extracted tooth, by an implant, fixed prosthesis, or removable partial dentures, may change the calculation in favor of RCT.